2012
DOI: 10.4100/jhse.2012.72.23
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the determination of anaerobic threshold: methodological survey on the modified Dmax method

Abstract: Siahkouhian M, Azizan S, Roohi BN. A new approach for the determination of anaerobic threshold: methodological survey on the modified D max method. J. Hum. Sport Exerc. Vol. 7, No. 2, pp. 599-607, 2012. A wide variety of diagnostic techniques can be found in the literature for anaerobic threshold (AT) assessment. The aim of this study was to investigate if the heart rate (HR) at the modified D max method (Mod-D max ) using parallel straight line slope (PSLS) mathematical model and the Narita target heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The inflexion point at which the distance between the line and the lactate regression curve is maximal is annotated as the D max value, and represents the threshold point at which a steady-state is reached between lactate production and elimination ( Zhou and Weston, 1997 ). Human studies report that the D max approach is suitable to define the individual lactate threshold to exercise and provides a good estimation of the MLSS ( Zhou and Weston, 1997 ; Siahkouhian et al, 2012 ; Zwingmann et al, 2019 ). In contrast, a study of Janeba et al (2010) , concluded that the D max approach is not a valid method because of the high dependence on the lowest and highest workload data points of the lactate curve ( Janeba et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflexion point at which the distance between the line and the lactate regression curve is maximal is annotated as the D max value, and represents the threshold point at which a steady-state is reached between lactate production and elimination ( Zhou and Weston, 1997 ). Human studies report that the D max approach is suitable to define the individual lactate threshold to exercise and provides a good estimation of the MLSS ( Zhou and Weston, 1997 ; Siahkouhian et al, 2012 ; Zwingmann et al, 2019 ). In contrast, a study of Janeba et al (2010) , concluded that the D max approach is not a valid method because of the high dependence on the lowest and highest workload data points of the lactate curve ( Janeba et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study of Janeba et al (2010) , concluded that the D max approach is not a valid method because of the high dependence on the lowest and highest workload data points of the lactate curve ( Janeba et al, 2010 ). Therefore, the Modified D max has been developed, though controversies regarding its ability or inability to estimate the MLSS remains ( Janeba et al, 2010 ; Siahkouhian et al, 2012 ; Płoszczyca et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%